2002
DOI: 10.4049/jimmunol.168.11.5530
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation Through Intercellular Adhesion Molecule-1 Provides a Second Signal for T Cell Activation

Abstract: Regulation of T cell activation requires two signals. First, appropriately presented Ag in the context of MHC interacts with the T cell Ag receptor-CD3 complex. The best-studied second signal is CD28, which resides on the T cell and responds to its counter receptor, B7. A second signal also can be delivered through LFA-1 residing on the T cell, responding to its counter receptor ICAM-1 residing on a different cell. Characterization of a second signal is tied to its ability to costimulate (along with stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
81
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 53 publications
2
81
0
Order By: Relevance
“…In addition to mediating ICAM-1 adhesion, it can generate outside-in signals that costimulate T cells (25,41,42). The nature of the outside-in pathway has been unclear, but may involve PYK-2 (proline-rich tyrosine kinase 2) and FAK (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to mediating ICAM-1 adhesion, it can generate outside-in signals that costimulate T cells (25,41,42). The nature of the outside-in pathway has been unclear, but may involve PYK-2 (proline-rich tyrosine kinase 2) and FAK (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…The ligation of ICAM-1 therefore represents an important event with the potential for greatly amplifying inflammation (15,51). Furthermore, in a recent study, signaling through ICAM-1 was shown to provide a co-stimulatory signal with that of CD3 leading to T cell proliferation and the induction of Th1 but not Th2 cytokines (52). In the present study, the pathways induced by binding to ICAM-1 were examined in detail to better understand the intracellular mechanisms involved in this response.…”
Section: Discussionmentioning
confidence: 99%
“…These molecules include LFA-1 (35) and ICAM (36) and these receptors may also use the mechanism of enhancing nuclear residence of NFATc1 to accomplish their costimulatory signals. nuc T cells.…”
Section: Discussionmentioning
confidence: 99%